FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN OBESITAS PADA ANAK USIA SEKOLAH - Rosmina Situngkir (Jurnal Keperawatan Florence Nightingale, 2018)
The higher prevalence of malnutrition and obesity in some areas will make the more complex burden and must be paid by the Indonesian people in developing some efforts in health, human and economic resources. This study aims to determine the relationship between some factors with obesity of children at the school age. This study is a non-experimental observational with cross sectional design. It is an accidental sampling with 50 respondents , the instruments used are questionnaires and observation sheets and analyzed by Chi-square test. By using the Chi square test and the approach of Kolmogorov-Sminov founded that the number of respondents with mild activity are four people (16%), while those who are not obese is 1 person (3.7%). Respondents with activity being obese as many as eight people (32%), while those not obese are six people (22.2%). Respondents with strenuous activities obese are 13 people (52%), while those who are not obese are 20 people (74.1%). The results show that the static test p = 0.552 and the value of ? = 0.05 this indicates that p> ? means that the factor of physical activity is not associated with obesity.